Popularization of off-season Coriander (Coriandrum Sativum L.) Cultivation in Eastern Ghat High Land Zone of Odisha - Sial, P.; Sahoo, B. B.; Behera, S. K.; Senapati, N. (Indian Journal of Hill Farming, 2016)
Coriander grows best in dry climates however it can grow in any type of soil like light, well drained, moist, loamy soil, and light to heavy black soil. The Eastern Ghat High Land Zone of Odisha is highly favourable for off-season coriander cultivation. The field experiments were conducted under Central Sector Scheme of National Horticulture Mission programme operating at High Altitude Research Station (OUAT), Pottangi of Koraput district of Odisha during Kharif2013-14 as front line demonstration in a sizeable farmer’s field of 20 advanced beneficiaries from different villages of Pottangi block in Koraput district. High yielding hybrid coriander seeds were supplied to the farmers along with different organic inputs like FYM, vermicompost and neem cake to popularize the technology. Results of the front line demonstration (FLD) revealed that the gross return (Rs.20,675) as well as the net return (Rs.6,855/-) obtained by the coriander growers under different FLDs are comparatively higher than that of farmers practice. Here it can be suggested that with optimum input cost and optimum changes in technology, it can be easily acceptable and validate for the long term benefit by the coriander growers.